THE RELATIONSHIP OF KNOWLEDGE WITH THE LEVEL OF PRE-OPERATIVE ANXIETY IN PATIENTS GENERAL ANESTHESIA - Ratih Kusuma Dewi (Keperawatan Anestesiologi Program Sarjana Terapan, 2024)
ABSTRACT Background: General anesthesia is a loss of consciousness caused by pharmacological induction which causes loss of sensory reflexes. General anesthesia is a technique that is often used, more than 80% of operations use general anesthesia compared to other anesthesia techniques. General anesthesia often causes anxiety in patients. Pre-operative anxiety is a condition associated with fear before surgery. Methods: The research design used is descriptive quantitative with a cross sectional research design. The population in this study were all surgical patients with general anesthesia at PKU Muhammadiyah Yogyakarta. The sampling technique used was purposive sampling with a sample size of 50 people. Univariate data analysis was carried out to see the frequency distribution and bivariate analysis used the chi-square test. Results: The research results showed that the majority of respondents, namely 66%, had little knowledge about surgery and 24% of respondents experienced serious anxiety about undergoing surgery. The results of the chi-square test showed a p value of 0.000 (p<0,05) with a percentage of relationship accuracy of 64,7%. Conclusion: The conclusion from the results obtained is that there is a close relationship between patient knowledge and the level of pre-operative anxiety in general anesthesia patients